2020
DOI: 10.1089/scd.2019.0301
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic Machine Perfusion Combined with Bone Marrow Mesenchymal Stem Cells Improves the Oxidative Stress Response and Mitochondrial Function in Rat Donation After Circulatory Death Livers

Abstract: There is a need to improve the quality of donor liver from donation after circulatory death (DCD). The purpose of this study was to investigate the effects and mechanism of normothermic machine perfusion (NMP) combined with bone marrow mesenchymal stem cells (BMMSCs) on the oxidative stress and mitochondrial function in DCD livers. DCD livers were obtained, a rat NMP system was established, and BMMSCs were extracted and identified. The DCD livers were grouped by their preservation method: Normal, static cold s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…The NMP system we used in this study was a self-modified single-cycle system. Based on our previous studies, the donor liver function was best at 6 h perfusion by the NMP system [ 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NMP system we used in this study was a self-modified single-cycle system. Based on our previous studies, the donor liver function was best at 6 h perfusion by the NMP system [ 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation, culture, identification, and gene transfection of BMMSCs were carried out as described previously [ 9 , 10 ]. Bone marrow contents were extracted from the rat femur and tibia, and BMMSCs were obtained by the continuous adhesion method [ 13 ]. Adenovirus vectors were used to transfect BMMSCs with constructs expressing the green fluorescent protein (GFP) and/or HO-1.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of MSCs with NMP resulted in the reduction of the levels of MPO and MDA and mitochondrial damage; increased the production of GSH; and ameliorated DCD liver oxidative stress injury. The study data also provided evidence that the normal functioning of the JNK/NF-κB and AMPK pathways was restored after MSC perfusion, both of which are known to be closely related to oxidative stress (Yang et al 2020a , 2020b ). Additionally, regardless of oxidative stress, disorders in the donated liver microcirculatory structure and function are other factors that considerably affect the liver physiological function post-transplantation (Vollmar and Menger 2009 ).…”
Section: Experimental Data On Combination Of Mesenchymal Stromal Cellmentioning
confidence: 63%
“…The same group reported that MSCs plus NMP pre-transplantation could also demonstrate this aspect of benefit. By inhibiting macrophage activation, by reducing microvascular leukocyte aggregation, by alleviating endothelial cell injury and by regulating ET-1/NO imbalance, this strategy effectively alleviates hepatic sinusoid congestion, maintains hepatic microcirculation homeostasis and favors the improvement of DCD liver quality (Yang et al 2020a , 2020b ).…”
Section: Experimental Data On Combination Of Mesenchymal Stromal Cellmentioning
confidence: 99%